Phytochemical Screening and in Vitro Evaluation of the Antibacterial Activity of Organic Extracts from the Root Bark of Cussonia arborea (Araliaceae) - Marlyse Moungang, Luciane; Sidjui Sidjui, Lazare; Narcisse Bayaga, Hervé; Ndambedia Mfouapon, Josséline; Nguélé, Ondoua; Kamga Gonsu, Hortense; Ngameni, Bathélemy (Journal of Applied Biotechnology, 2021)
Objective: To assess the usefulness of Cussonia arborea in the treatment of bacterial infectious diseases. Study Design: Experimental analytical study. Place and Duration of Study: The study was done in the Laboratory of Hydrobiology and Environment of the Faculty of Science, University of Yaounde1; the Bacteriology Laboratory of the Yaoundé University Teaching Hospital; the Laboratory of Pharmacognosy and Pharmaceutical Chemistry of the Faculty of Medicine and Biomedical Sciences and the Laboratory of Organic Chemistry of the Faculty of Sciences of the University of Yaoundé I. The study was done in a period of six months. Methodology: The root bark of Cussonia arborea was collected in the village Yambéta (Central Region, Cameroon), dried and pulverized. Thereafter, two extractions were performed by embedding 200 g of powder in 2000 mL of 96° ethanol, and in a hydro-ethanolic mixture (30/70, v/v), respectively. Qualitative phytochemical screening was performed. Minimum inhibitory and bacterial toxicity were determined by macro-dilution in liquid medium on Staphylococcus aureus, Salmonella sp, Shigella sp and Proteus mirabilis provided by the Laboratory of Hydrobiology and Environment of the Faculty of Science, University of Yaounde1 and the Bacteriology Laboratory of the Yaoundé University Teaching Hospital. Results: Phytochemical screening revealed the presence of polyphenols (flavonoids, and tannins), alkaloids, quinones, saponins and, cardiac glycosides. However, coumarins were absent in the two extracts. The minimum inhibitory concentrations of the extracts ranged from 25 to 100 mg/mL, and the minimum bactericidal concentrations from 25 to 200 mg/mL. The ethanolic extract was bactericidal against Proteus mirabilis and Staphylococcus aureus, but bacteriostatic against Salmonella sp and Shigella sp. The hydro-ethanolic extract was bacteriostatic against Shigella sp and bactericidal against the other strains. Conclusion: The groups of polyphenols, alkaloids, quinones, saponins and, cardiac glycosides contained in the two extracts can justify the antibacterial activity observed against Staphylococcus aureus, Salmonella sp, Shigella sp and Proteus mirabilis.